Mapping the Interplay between Open Distance Learning and Internationalisation Principles - Msweli, Pumela (International Review of Research in Open and Distributed Learning, 2012)
Open distance learning is viewed as a system of learning that blends student support, curriculum and instruction design, flexibility of learning provision, removal of barriers to access, credit of prior learning, and other academic activities such as programme delivery and assessment for the purpose of meeting the diverse needs of students. Internationalisation, on the other hand, is viewed as a process that blends intercultural international dimensions into different academic activities, such as teaching, learning, and research, into the purpose and functions of higher education. The common feature in the narratives that define open distance learning and internationalisation is the blending of university services to achieve specific outcomes. This blending feature has instigated an inquiry into identifying the interplay between the two concepts in as far as how the concepts are defined and what their goals and rationale are in the context of higher education institutions. While there are a breadth and variety of interpretations of the two concepts, there are differences and common features. The purpose of such an analysis is to open a new window through which institutions of higher learning can be viewed.